Highly sensitive photoacoustic multi-gas analyzer combined with mid-infrared broadband source and near-infrared laser. (January 2020) - Chen, Ke; Liu, Shuai; Zhang, Bo; Gong, Zhenfeng; Chen, Yewei; Zhang, Ming; Deng, Hong; Guo, Min; Ma, Fengxiang; Zhu, Feng; Yu, Qingxu
Highlights: A high sensitive PA multi-gas analysis method combined with mid-infrared broadband source and near-infrared laser is presented. It takes full advantage of the multi-component gas measurement capability of mid-infrared broadband source based PAS and the high precision of laser-based PAS. A multi-pass cylindrical PA cell is designed to efficiently couple the two PA excitation lights. The detection limits of C2 H2, CO, CO2, CH4, C2 H6 and C2 H4 are achieved to ppb-level. Abstract: A highly sensitive photoacoustic (PA) multi-gas analyzer was developed in combination with a mid-infrared broadband source and a near-infrared laser. A multi-pass cylindrical PA cell was designed to efficiently couple the two PA excitation sources. The mid-infrared thermal radiation light was transmitted into the longitudinal direction of the cell for detecting CO, CO2, CH4, C2 H6, C2 H4 and H2 O gas. The fundamental-frequency intensity modulation (1 f -IM) technique was used to measure the generated PA signal. The collimated near-infrared laser beam was incident from the side hole of the cell for detecting C2 H2 gas. The second-harmonic wavelength modulation spectroscopy (2 f -WMS) technique was used to extract the laser-excited PA signal. The noise equivalent detection limits (1 σ ) were achieved to be 27 ppb, 10 ppb, 94 ppb, 24 ppb, 20 ppb and 37 ppb for C2 H2, CO, CO2, CH4, C2 H6 and C2 H4 with an averaging time of 60 s, respectively. The proposed method takes full advantage of the multi-component gas measurement capability of mid-infrared broadband source based PA spectroscopy (PAS) and the high precision of laser-based PAS.